"I've been to physical therapy before, but not for the knees." A qualitative study exploring barriers and facilitators to physical therapy utilization for knee osteoarthritis. (26th June 2020) - Christiansen, Meredith B.; Dix, Celeste; Master, Hiral; Jakiela, Jason T.; Habermann, Barbara; Silbernagel, Karin G.; White, Daniel K.
Abstract: Background: Physical therapy (PT) is recommended to reduce pain and improve function. However, only 10%–15% of adults with knee osteoarthritis (OA) use PT in the United States. The purpose of this study was to explore patient‐reported barriers and facilitators to PT utilization for knee OA, to understand why PT is underutilized. Methods: Qualitative descriptive study using semi‐structured interviews was conducted, that is, one‐on‐one phone interviews with adults from local community centers. Participants were eligible if they were fluent in English and self‐reported knee OA (1) over 45 years of age, (2) have activity‐related knee pain, and (3) have no morning stiffness or morning stiffness in the knee(s) for ≤30 min. Interviews were audio‐recorded and transcribed. To identify barriers and facilitators to PT utilization for knee OA, a coding framework, thematic analysis, and a constant comparative approach were used. Results: Of 22 participants with health insurance and who participated, 59% were considering PT, 23% refused PT, and 18% used PT for knee OA. Themes identified as either barriers or facilitators for participants were (1) previous experience with PT, (2) physician referral, (3) beliefs about treatment efficacy before and after knee replacement surgery, (4) insurance coverage, and (5) preference to avoid surgery. Conclusion: A previous positive encounter with PT and a physician referral may facilitate PT utilization for adults with knee OA. Knowledge about and access to PT services were not identified as barriers related to PT utilization. Further research is necessary to confirm findings in a broader group of adults with knee OA.